The Modern Tower of Babel - Wilson, Colonel Harry A. (Academy of Management Journal, 1970)
The article reports the author's opinions regarding a U.S. Air Force conference held at the Air Academy. The author focuses on difficulties he had understanding some of the language used by speakers at the conference. It is suggested that the current usage of acronyms, abbreviations, and initials within the U.S. Air Force is creating a situation comparable to that of the Biblical story of the Tower of Babel.